Information Needs of teachers on Students with Dysgraphia - Adaramola, Temitope A.; Ujulu, Philip J.; Ayodele, Tosin A. (POMLIF Journal of Library and Information Science, 2021)
The paper discussed the information needs of teachers on students with dysgraphia disorder. Students with dysgraphia disorder are most times being overlooked by teachers; hence this paper gives insight on the meaning, causes, symptoms and effects of dysgraphia. The paper therefore recommends among others that libraries should endeavor to provide assistive technology software to both teachers and students on dysgraphia such as games, illustrated books etc also dysgraphia children, their families and teachers should be provided with information and education about dysgraphia disorder and its impact, and the advantages and disadvantages of potential treatment strategies.